1994
DOI: 10.1002/eat.2260150409
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the eating disorders inventory in a nonclinical population using transformed and untransformed responses

Abstract: In the present study, the validity of the Eating Disorder Inventory (€01) in a Dutch nonclinical female school population was established. The data were analyzed in two Ways. In the first analyses, the factorial integrity of the questionnaire, and the internal consistencies of the subscales were not found to be very satisfactory. The data showed an impressive lack of variability. It was suggested by the authors that in a nonclinical Population the variability ofthe ED1 data is being suppressed as a result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(90 citation statements)
references
References 12 publications
4
82
1
2
Order By: Relevance
“…41 Patients with obesity presented strong negative feeling about their bodies. 42 The present survey showed that age did not demonstrate any impact an the scores on the questionnaire EDI, except that the younger group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) showed significantly higher scores than the middle aged group (40-49) on subscale bulimia on the questionnaire EDI-2. Mclean, Paxton and Wertheim found that in the EDE-Q subscales: the Body Dissatisfaction and disordered eating symptoms were unrelated to age 13 .…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…41 Patients with obesity presented strong negative feeling about their bodies. 42 The present survey showed that age did not demonstrate any impact an the scores on the questionnaire EDI, except that the younger group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) showed significantly higher scores than the middle aged group (40-49) on subscale bulimia on the questionnaire EDI-2. Mclean, Paxton and Wertheim found that in the EDE-Q subscales: the Body Dissatisfaction and disordered eating symptoms were unrelated to age 13 .…”
Section: Discussioncontrasting
confidence: 54%
“…But several authors have argued that the original scoring is in fact better [31][32][33] . Shoemaker et al discovered that compared to the transformed scales 0-3, the original 1-6 scoring showed a higher internal consistency 32 (cited by 34 ).…”
Section: Edi-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Because this was a nonclinical population, responses were scored using the untransformed scale (Schoemaker, van Strien, & van der Staak, 1994).…”
Section: Eating Disorder Inventorymentioning
confidence: 99%